Determinants of Bank Interest Margins in Sub-Saharan Africa - Ahokpossi, Calixte (IMF Working Papers; Working Paper ;, 2013)
Financial intermediation is low in sub-Saharan Africa (SSA) compared to other regions of the world. This paper examines the determinants of bank interest margins using a sample of 456 banks in 41 SSA countries. The results show that market concentration is positively associated with interest margins, but the impact depends on the level of efficiency of each bank. In particular, compared to inefficient banks, efficient ones increase their margins more in concentrated markets. This indicates that policies that promote competition and reduce market concentration would help lower interest margins in SSA. The results also show that bank-specific factors such as credit risk, liquidity risk, and bank equity are important determinants of interest margins. Finally, interest margins are sensitive to inflation, but not to economic growth or public or foreign ownership. There are regional differences within SSA regarding the level of interest margins even after controlling for other factors.